Association between heme oxygenase-1 and hyperlipidemia in pre-diabetic patients: a cross-sectional study - Fan, Shujin; Yang, Yulin; Li, Xiaoyu; Liu, Jing; Qiu, Yue; Yan, Li; Ren, Meng (Frontiers in Endocrinology, 2024)
Although the importance and benefit of Heme oxygenase-1 (HO-1) in diabetes rodent models has been known, the contribution of HO-1 in the pre-diabetic patients with hyperlipidemia risk still remains unclear. This cross-sectional study aims to evaluate whether HO-1 is associated with hyperlipidemia in pre-diabetes.Serum level of HO-1 was detected using commercially available ELISA kit among 1425 participants aged 49.3 to 63.9 with pre-diabetes in a multicenter Risk Evaluation of cAncers in Chinese diabeTic Individuals: A lONgitudinal(REACTION) prospective observational study. Levels of total cholesterol (TC) and triglyceride (TG) were measured and used to defined hyperlipidemia. The association between HO-1 and hyperlipidemia was explored in different subgroups.The level of HO-1 in pre-diabetic patients with hyperlipidemia (181.72 ± 309.57 pg/ml) was obviously lower than that in pre-diabetic patients without hyperlipidemia (322.95 ± 456.37 pg/ml). High level of HO-1([210.18,1746.18] pg/mL) was negatively associated with hyperlipidemia (OR 0.60, 95% CI, 0.37-0.97, P = 0.0367) after we adjusted potential confounding factors. In subgroup analysis, high level of HO-1 was negatively associated with hyperlipidemia in overweight pre-diabetic patients (OR 0.50, 95% CI, 0.3-0.9, P = 0.034), especially in overweight female (OR 0.42, 95% CI, 0.21-0.84, P = 0.014).In conclusions, elevated HO-1 level was negatively associated with risk of hyperlipidemia in overweight pre-diabetic patients, especially in female ones. Our findings provide information on the exploratory study of the mechanism of HO-1 in hyperlipidemia, while also suggesting that its mechanism may be influenced by body weight and gender.